Studies on fertilization of dill (Anethum graveolens L.) and basil (Ocimum basilicum L.) lll Oil yield of basil affected by fertilization - Hälvä, S. (Agricultural and Food Science, 1987)
Basic fertilization and nitrogen top-dressing of basil was studied in 1984 and 1985 at the Department of Horticulture, University of Helsinki. The total N doses applied were 0, 0.2, 0.4, 0.8, 1.2 and 1.6 kg N/100 m2. In 1984 the plants were of a mixture of different fenotypes and two of those formed 85 % of the crop-stand. In 1985 the variety grown was ’Budakalasz’. The optimum basic fertilization proved to be a compound fertilizer at the rate (NPK) of 0.4—0.16—0.68 kg/100 m2. The content of volatile oils in dried herb ranged from 0.32 to 1.46 %. The total oil content was not significantly affected by fertilization except in 1984 when the fertilization decreased the oil content in the other of those two major fenotypes.